Regulatory induced performance persistence: Evidence from hedge funds - Cumming, Douglas; Dai, Na; Haß, Lars Helge; Schweizer, Denis (Journal of Corporate Finance, 2012)
This paper tests the idea that financial regulation can impact performance persistence in the context of the hedge fund industry in 48 countries over the years 1994–2008. The data show evidence of three types of regulation influencing performance persistence: (1) minimum capital restrictions, which restrict lower quality funds and hence increase the likelihood of performance persistence, (2) restrictions on location of key service providers, which restrict human capital choices and hence tend to mitigate performance persistence, and (3) distribution channels, which make fund performance more opaque, decrease the likelihood of performance persistence. We do not find evidence that distribution channels, that promote fund presence to institutional investors, enhance performance persistence. Finally, we show differences in the effect of regulation on persistence by fund quartile ranking.